Correlation between Substance Use and Anxiety-Depression Spectrum among Senior High School Students in Bandung - Achmad Samjunanto; Lucky Saputra; RA. Retno Ekowati (Althea Medical Journal, 2016)
Background: Both substance use and anxiety-depression spectrum are the problem that currently faced by adolescents especially among Senior High School students. Moreover, there is a high comorbidity between both problems. This study was conducted to discover the substance use’s prevalence and to find out anxiety-depression spectrum proportion among adolescent, and more importantly to determine whether there is correlation between both variables.Methods: During October–November 2013, four hundred and fifty two students from five Senior High Schools located in Karees Sub-District, Bandung were included in this cross-sectional analytic study. Among whom, only 425 students filled the questionnaire properly. Data were collected using Kessler-10 (K10) to explore anxiety-depression spectrum and addiction severity index lite version (ASI-Lite) to identify substance use. The correlation between both variables was analyzed by Gamma correlation test.Results: The study revealed that there were 93 (21.9%) students that used substance. In addition, there were 244 students (57.4%) that screened as having anxiety-depression spectrum. Statistical analysis, according to Gamma correlation test, showed that there was a weak correlation between alcohol use and anxiety-depression spectrum (p=0.041; r=0.316). The remaining substances gave no statistically significant result (p>0.05). Conclusions: There is a high prevalence in substance use and psychological distress in anxiety-depression spectrum among high school student. In addition, alcohol is the only substances that correlated with anxiety-depression spectrum. [AMJ.2016;3(4):583–9] DOI: 10.15850/amj.v3n4.943